Catalpol Exerts a Neuroprotective Effect in the MPTP Mouse Model of Parkinson’s Disease - Wang, Li-Yuan; Yu, Xin; Li, Xiao-Xi; Zhao, Yi-Nan; Wang, Chun-Yan; Wang, Zhan-You; He, Zhi-Yi (Frontiers in Aging Neuroscience, 2019)
The degeneration of dopaminergic (DA) neurons in Parkinson’s disease (PD) is related to inflammation and oxidative stress. Anti-inflammatory agents could reduce the risk or slow the progression of PD. Catalpol, an iridoid glycoside extracted from the roots of Rehmannia radix, has been reported to reduce the release of inflammatory factors and exert neuroprotective effects. 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-treated mice were used as the PD model and the roles of catalpol on DA neurons and its potential mechanism were investigated in this study. We found that catalpol administration mitigated the loss of DA neurons induced by MPTP and increased exploratory behavior along with tyrosine hydroxylase expression, which was accompanied by astrocyte and microglia activation. Importantly, catalpol administration significantly inhibited MPTP-triggered oxidative stress, restored growth-associated protein 43 (GAP43) and vascular endothelial growth factor (VEGF) levels. Further, we found that catalpol suppressed the activation of MKK4/JNK/c-Jun signaling, and reduced the pro-inflammatory factors and inflammasome in the mouse model of PD. Our results suggest that catalpol relieves MPTP-triggered oxidative stress, which may benefit to avoid the occurrence of chronic inflammatory reaction. Catalpol alleviates MPTP-triggered oxidative stress and thereby prevents neurodegenerative diseases-related inflammatory reaction, highlighting its therapeutic potential for the management of PD symptoms.